Enhanced electronic and optical responses of nitrogen- or boron-doped BeO monolayer: First principle computation. (February 2022) - Abdullah, Nzar Rauf; Abdullah, Botan Jawdat; Rshid, Hunar Omar; Tang, Chi-Shung; Manolescu, Andrei; Gudmundsson, Vidar
Abstract: In this work, the electronic and optical properties of a Nitrogen (N) or a Boron (B) doped BeO monolayer are investigated in the framework of density functional theory. It is known that the band gap of a BeO monolayer is large leading to poor material for optoelectronic devices in a wide range of energy. Using N or B dopant atoms, we find that the band gap can be tuned and the optical properties can be improved. In the N(B)-doped BeO monolayer, the Fermi energy slightly crosses the valence (conduction) band forming a degenerate semiconductor structure. The N or B atoms thus generate new states around the Fermi energy increasing the optical conductivity in the visible light region. Furthermore, the influences of dopant atoms on the electronic structure, the stability, the dispersion energy, the density of states, and optical properties such as the plasmon frequency, the excitation spectra, the dielectric functions, the static dielectric constant, and the electron energy loss function are discussed for different directions of polarizations for the incoming electric field. Highlights: Boron or Nitrogen dopant atoms decreases the band gap of BeO monolayer. Boron or Nitrogen atoms generated new states in BeO monolayer. The new states enhances electronic and optical properties. Strong enhancement in optical behaviors in visible ligh region is seen. Nitrogen- or Boron-doped BeO can strongly improve plasmon oscillation.